Remote Patient Monitoring Pada Pasien Kanker: Analisis Konsep - Ashar Prima; Dewi Gayatri; Yati Afiyanti; Christantie Effendy (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Background. Remote Patient Monitoring (RPM) has emerged as an innovative approach in healthcare, particularly for monitoring patients with chronic conditions such as cancer. Variations in approaches in research and clinical practice can lead to differences in interpretation among healthcare professionals and researchers. Research Objectives. This study aims to explore the concept of remote patient monitoring. Method. Concept analysis was conducted following the eight-step approach by Walker and Avant: selecting the concept, determining the purpose of the analysis, identifying all uses of the concept, determining defining attributes, identifying model cases, identifying borderline and contradictory cases, identifying antecedents (preceding factors) and consequences, and defining empirical referents. A literature review was conducted using the Google Scholar, Scopus, ScienceDirect, EBSCOhost, and ProQuest databases to identify articles published between 2018 and 2024. Results. The analysis identified five main attributes of RPM: continuous monitoring, technology integration, multidisciplinary collaboration, service accessibility, and patient-centered care. These attributes are theoretically associated with positive consequences such as early detection of complications, improved health outcomes, cost-effectiveness, and patient empowerment and quality of life. Preceding factors include the availability of digital technology and infrastructure, the healthcare needs of cancer patients, challenges in accessing healthcare services, and patients' digital literacy and readiness. Conclusion. This study contributes theoretically by providing a conceptual model of RPM that can serve as a foundation for developing digital nursing practices and RPM implementation policies in oncology services. Standardizing the definition and conceptual modeling of RPM is crucial to ensuring consistent and effective integration within cancer patient care systems, where nurses play a central role in data interpretation and interprofessional coordination. Keywords: Remote Patient Monitoring; Cancer Patients